Factores de riesgo de parto pretermino en el hospital belén de trujillo, 2009 - 2013 - Cotera Orbegozo, Sarvia Inés (2014)
Preterm birth occurs between 22 and before 37 weeks; the incidence in Peru varies between 5.6% and 14% of all pregnancies and remains one of the biggest problems of morbidity and infant and maternal mortality. Objective: Determine whether a history of preterm delivery, adolescent maternal age, anemia and infection pathways are risk factors for the development of preterm delivery in pregnant women at the Bethlehem Hospital of Trujillo, January 2009-December 2013. Material and Method: An observational, retrospective case-control study, the January 1, 2009 to December 31, 2013 was performed. Cases: 285 pregnant women who completed their pregnancy between 22 weeks and before 37 weeks. Controls: 285 pregnant women who completed their pregnancy between 37 weeks and 41 weeks 6 days. The data obtained were processed in Microsoft Excel using the tools: two-ways tables and bar graph to represent the data. For statistical analysis, the odds ratio test statistic was used, chi square and logistic regression using the SPSS 22.0 program. Results: With respect to the variable “history of preterm birth”, the occurrence was 15.4% (cases) and 5.6% (controls); the “anemia” factor occurred in 21.1% (cases) and 13.3% (controls); “Adolescent maternal age” was featured in 29.5% (cases) and 24.9% (controls) and “urinary tract infection” was featured in 3.2% (cases) and 2.8% (controls). Were significantly associated factors: a history of preterm delivery (OR 3.070, p<0.0001) and anemia (OR 1.733, p<0.015). After applying logistic regression with significant risk factors found that only the variable history of preterm birth is a risk factor for preterm birth in Bethlehem Hospital of Trujillo of January 1, 2009 to December 31, 2013 Anemia, adolescent maternal age and urinary tract infections were not statistically significant as the risk factors associated preterm birth